Legitimation in action: an examination of community courts and procedural justice - Connor, Tyrell A. (Journal of crime and justice, 2019)
We are at a critical moment in criminal justice reform as public distrust grows and threatens the legitimacy of the justice system. This is especially true for poor communities of color who have lower levels of trust because they have been disproportionately involved in the system, compared to their white counterparts. Community courts represent one way to restore trust and legitimacy in our criminal justice system. Although community courts are gaining popularity among policymakers, there has been little research about them. Using the theoretical framework of procedural justice, this study examines the way community courts attempt to achieve such reform. Observations, field notes, and interviews were taken over a three-month time period in three community courts: Midtown, Red Hook, and Newark. The findings illustrate the various ways judges in community courts practice and apply principles of procedural justice. Furthermore, this paper highlights findings that demonstrate how certain courtroom practices and procedures may be potentially problematic to procedural justice. Policy implications of this paper give advice on the ways community courts can strengthen their use of procedural justice in order to maintain legitimacy and trust in communities.